2009
DOI: 10.4314/gjpas.v15i3-4.48561
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity and medicinal properties of ginger (<i>Zingiber officinale</i>)

Abstract: The antibacterial activity and medicinal properties of ginger extracts were studied. Ginger extracts were obtained using solvents, n-hexane, ethyl acetate, ethanolic soxhlet and water. The extracts were assayed for antibacterial activity and bacterial growth inhibition activity. The results showed that all the extracts except the water extract have antibacterial activity and that the inhibition of bacterial growth was dose dependent. The results also showed that ginger extracts possesses antibacterial properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 5 publications
6
53
0
8
Order By: Relevance
“…The terpenoids are one of significant substances in pharmacy due to their connection with such compounds as vitamin A and have wide range of application in medicen. The gingerols could make ginger available for treatment of stomach acidity and may have analgesic and sedative properties (Malu et al 2009). …”
Section: Resultsmentioning
confidence: 99%
“…The terpenoids are one of significant substances in pharmacy due to their connection with such compounds as vitamin A and have wide range of application in medicen. The gingerols could make ginger available for treatment of stomach acidity and may have analgesic and sedative properties (Malu et al 2009). …”
Section: Resultsmentioning
confidence: 99%
“…[1] Zingiberene is one of the major volatile oil present in the ginger extract along with sequesterpene, which causes the fragrance of the spice. [9] Successful prediction of bioactive compounds from plant material is largely dependent on the type of solvent used in the extraction procedure. In addition to the intrinsic bioactivity of the compound, the polarity of the compounds extracted from the solvent determines the ability to dissolve or diff use in the diff erent media used in the assay.…”
Section: Discussionmentioning
confidence: 99%
“…They also reported that antimicrobial activity of the ethanol extract of ginger, lime and garlic against a broad range of bacteria including Bacillus spp., Staphylococcus aureus, Escherichia coli, and Salmonella spp. In another study, Malu et al [105] have carried out the antibacterial activity of ginger extracts. In their experiment, they obtained ginger extracts using solvents, n-hexane, ethyl acetate, ethanolic soxhlet and water.…”
Section: Antimicrobial Activitiesmentioning
confidence: 99%